Dicranopteris linearis (Burm. F) Underw.: Catatan Baru Database Tumbuhan di Cagar Alam/Taman Wisata Alam Kawah Ijen, Indonesia - Andik Wijayanto; Suhadi Suhadi; Murni Saptasari; Dyah Ayu Pitaloka; Fira Fitria Jihans; Muhammad Hisyam Baidlowi; Eko Sri Sulasmi (Universitas Negeri Malang, 2019)
It is important to carry out exploration of pteridophyte biodiversity in Ijen Crater Nature Preserve because with extreme natural conditions, we expected to get potential species for medicine purpose. In addition, knowing the diversity and abundance of a species becomes a conservation consideration. We found only one species of the genus Dicranopteris, i.e. Dicranopteris linearis (Burm. F) Underw. with low abundance (4-10 individuals per cluster) and only found in one location. This shows that this species needs attention due to its rarity in the area and further phytochemical analysis is needed to determine its potential as a drug.